Factores asociados al alto rendimiento académico de los estudiantes de Pedagogía de las Ciencias Experimentales: Matemáticas y la Física de la UNACH. - Cueva Lucero, Brithany Anayeli (2024)
The objective of this research work is to reveal the factors associated with the high academic performance of the students of the Pedagogy of Experimental Sciences: Mathematics and Physics. Regarding the methodology, a qualitative approach was used since the information collected is descriptive, it has a non-experimental design because the data were not manipulated, a descriptive level was applied and also a field and transversal type of research was used since the place where the phenomenon is developed was visited and the interviews were carried out in a certain time. The analysis of four informant subjects with high performance was carried out; Atlas ti was used for the analysis of the interviews. The results of the interviews showed that the informants are between 24 and 27 years of age, their parents have and do not have a degree. Three of the four students seek feedback and spend 3 to 4 hours on self-study. None of the four has demonstrated that their economic situation influences their high performance, but it is more complicated to reach that achievement. The university's infrastructure and technological tools also influence their academic performance. Constant stress and pressure is part of life for three of these students. Extracurricular activities influence their high performance. The teacher's motivation also has a positive influence. In conclusion, this study highlights the complexity of becoming a high-achieving student, which ranges from the family, socioeconomic, social and emotional factors, to the university itself with its infrastructure and teaching. It is recommended that a more in-depth study be conducted with students of low and medium performance to identify the differences that exist in terms of parents' schooling, place of origin, study habits, infrastructure and technology, socioeconomic level, and social factor, as well as for future studies, emotional and psychological studies should be conducted on students to obtain a broader approach and to be able to contribute with effective guidelines for high-performing students to maintain academic success